2012
DOI: 10.1055/s-0032-1301392
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Following Endoscopic Resection of Skull Base Tumors

Abstract: There has been an increasing acknowledgment of the importance of topics addressing the quality of life (QOL) of patients with cancer. QOL is assessed in an effort to improve treatment modalities, to promote restoration of the patient's daily function, and to accelerate his return to normal life. Estimation of the influence of specific surgical procedures on QOL can serve as a means by which the most appropriate surgical approach can be selected for a given patient, especially when no single modality has a clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 18 publications
3
36
2
2
Order By: Relevance
“…Recent case studies on endoscopic skull base surgery evaluating QOL (using the ASBS-Q) have described the female sex as a significant predictor of a poor outcome. 3 Our data do not confirm this difference. Similarly, Palme et al did not find sex to be a prognostic factor, although they used tools different from ours.…”
Section: Discussioncontrasting
confidence: 80%
“…Recent case studies on endoscopic skull base surgery evaluating QOL (using the ASBS-Q) have described the female sex as a significant predictor of a poor outcome. 3 Our data do not confirm this difference. Similarly, Palme et al did not find sex to be a prognostic factor, although they used tools different from ours.…”
Section: Discussioncontrasting
confidence: 80%
“…The ASBQ was subsequently demonstrated to have psychometric validity for site-specific QOL assessment following anterior skull base surgery for both transcranial and endoscopic approaches. 4,17 A prospective study of QOL in patients undergoing open anterior skull base surgery has only recently been described. Abergel et al assessed a series of 39 patients with the ASBQ prior to surgery and again at 2 postoperative points.…”
Section: Discussionmentioning
confidence: 99%
“…44 Although the ASBQ was originally intended to assess QOL after craniotomy for anterior skull base lesions, it was recently validated for endonasal endoscopic surgery. 4 In addition, by using this measure, our results can be compared with ASBQ outcomes after craniotomy published in the literature. Both questionnaires were filled out by the patient, either in the office or through a phone interview.…”
Section: Quality Of Life Assessmentmentioning
confidence: 99%
“…While the validation cohort was treated exclusively via open, nonendoscopic surgical approaches, the ASBQ has recently been validated for endoscopic approaches as well. 4 Multiple studies have demonstrated the validity of the ASBQ for anterior skull base surgery and the association of ASBQ scores with outcomes and other factors including pathology, approach, age, and degree of resection.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has validated the use of the ASBQ to assess endoscopic surgical outcomes, with 75% of cases reporting improvement or no change in overall QOL. 4 Reconstruction of the postoperative skull base defect is an important consideration in all cases regardless of surgical approach. Achieving low rates of postoperative CSF leak following endoscopic surgery has been well demonstrated with more recent publications in the literature.…”
mentioning
confidence: 99%